Human Rights-Based Legal Protection for Sexual Violence Victims in Formal Education - Kurniawan, Fakhrul; Munawar, Iwa; Suparman, Odang (LifeSciFi, 2025)
Sexual violence in formal educational institutions continues to pose a serious problem, with numerous documented victims experiencing psychological trauma, academic decline, and violations of fundamental human rights. This phenomenon highlights the urgent need for comprehensive and systemic protection mechanisms. The purpose of this study is to examine the legal protection afforded to victims and witnesses of sexual violence in formal education settings from the perspective of human rights, particularly as regulated under Law Number 39 of 1999 on Human Rights. This research uses a qualitative approach with a juridical-normative method through library research. The findings indicate that legal protection has not been effectively implemented due to weak inter-agency coordination, lack of socialization, and limited institutional resources. In many cases, the institutional culture prioritizes reputation over justice, resulting in closed mediation processes that ignore victims' rights. Educational services are also often partial and unsustainable, further aggravating victim trauma. The study concludes that legal protection in educational settings still deviates from human rights principles, necessitating stronger regulatory enforcement and cooperation between policy makers and law enforcement to ensure justice and prevent recurring victimization.